India in Hindu eschatology: A survey on kerala bhakti literature - Munawar Hanih Thottathodi (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This Research article analyzes the eschatological aspects of Kerala’s Bhakti literature to elucidate how devotional texts reflect India’s spiritual and political self-perception. This study is situated within the expansive domain of Hindu historical eschatology, examining the ways in which Bhakti poets like Ezhuthachan, Poonthanam Namboodiri, and Melpathur Bhattathiri reinterpreted scriptural concepts of Kaliyuga, moral decline, and salvation into vernacular forms that promote cultural renewal. Methods: The research utilizes a qualitative, interpretive methodology rooted in Gadamerian hermeneutic textual analysis. The study employs three analytical stages—textual exegesis, contextual interpretation, and conceptual synthesis—to identify key eschatological motifs, compare their manifestations across selected texts, and position them within Hindu philosophical cosmology and contemporary Indian political discourse. Findings: Comparative insights are also drawn between Hindu and Abrahamic ideas of apocalypse to elucidate the unique cyclical temporality and moral focus of Hindu eschatology. The findings indicate that Kerala’s Bhakti corpus reconceptualizes Kaliyuga not only as a mythical era of deterioration but also as a moral state wherein devotion emerges as the most straightforward and attainable route to redemption. Conclusion: These works further sanctify Bharath (India) as a redemptive geography—an eschatological realm where divine grace and moral regeneration converge. Bhakti literature serves as theology, moral philosophy, and proto-political discourse by connecting spiritual rebirth to India's historical resilience. The study's methodological constraint is its dependence on a restricted textual corpus, primarily Malayalam Bhakti works; yet, it lays the groundwork for further comparative research among different regional traditions. Novelty/Originality of this article: The article's originality is in the development of a conceptual model of Hindu historical eschatology, connecting devotional literature with political imagination, and illustrating how spiritual writings persist in influencing India's ethical and cultural modernity.